Unemployed people in search of a job: Reconsidering the role of search behavior - Šverko, Branimir (Array, 2008)
A three-wave longitudinal study of unemployed persons in Croatia was utilized to examine the antecedents of job-seeking behavior and (re)employment. A series of demographic, motivational and job-constraint variables were posited to influence job-seeking behavior, which, in turn, was hypothesized to affect (re)employment. The participants were surveyed in 2003 (N=1138), and their employment status was checked in 2004 (N=601) and 2005 (N= 452). Regression analyses supported only one slice of the model – the antecedent-job search relations. All motivational variables, in particular employment commitment and perceived financial strain, proved to be relatively strong predictors of job-search intensity. However, they appeared to be only weakly related to (re)employment outcome. Demographic variables – in particular education, age, and employment duration – appeared to be main determinants of (re)employment, operating presumably through their influence on employers' hiring decisions. Further research is suggested to examine why purposive and proactive activity of job searching does not pay more. The implication of these findings for research and practice are discussed.